Quaternary Ammonium Compounds: Simple in Structure, Complex in Application - Bureš, Filip (Topics in current chemistry, 2019)
Quaternary ammonium compounds, referred to as QACs, are cationic substances with a structure on the edge of organic and inorganic chemistry and unique physicochemical properties. The purpose of the present work is to introduce QACs and their wide application potential. Fundamental properties, methods of preparation, and utilization in organic synthesis are reviewed. Modern applications and the use of QACs as reactive substrates, reagents, phase-transfer catalysts, ionic liquids, electrolytes, frameworks, surfactants, herbicides, and antimicrobials are further covered. A brief discussion of the health and environmental impact of QACs is also provided. The emphasis is largely on tetraalkylammonium compounds bearing linear alkyl chains.
Keywords: kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; Herbicides; Anti-Infective Agents; povrchově aktivní látky; antiinfekční látky; Surface-Active Agents; herbicidy